Silencing the myotrophin gene by RNA interference leads to the regression of cardiac hypertrophy - Gupta, Sudhiranjan (American Physiological Society, 2009)
Myotrophin-induced activation of NF-κB has been shown to be associated with cardiac hypertrophy (CH) that progresses to heart failure (HF). In the present study, we examined the cause-and-effect relationship between myotrophin and NF-κB activation using small hairpin RNA (shRNA) against myotrophin both in vitro (using neonatal rat myocytes) and in vivo [using myotrophin transgenic (Myo-Tg) mice, which overexpress myotrophin in the heart, develop CH, and gradually progress to HF]. Among several lentiviral vectors expressing myotrophin shRNAs, L-sh-109 showed the best silencing effect at both the mRNA (155.3 ± 5.9 vs. 32.5 ± 5.5, P < 0.001) and protein levels associated with a significant reduction of atrial natriuretic factor (ANF) and NF-κB. In vivo, when L-sh-109 was delivered directly into the hearts of 10-wk-old Myo-Tg mice, we observed a significant regression of cardiac mass (8.0 vs. 5.7 mg/g, P < 0.001) and myotrophin gene expression (54.5% over untreated Myo-Tg mice, P < 0.001) associated with a reduction in ANF and NF-κB signaling components. Our data suggest that using RNA interference to silence the myotrophin gene prevents NF-κB activation, associated with an attenuation of CH. This strategy could be an excellent therapeutic means for the treatment of CH and HF.